Aberrant extracellular signal-regulated kinase (ERK)1/2 signalling in suicide brain: role of ERK kinase 1 (MEK1) - Dwivedi, Yogesh; Rizavi, Hooriyah S.; Zhang, Hui; Roberts, Rosalinda C.; Conley, Robert R.; Pandey, Ghanshyam N. (The international journal of neuropsychopharmacology, 2009)
Extracellular signal-regulated kinase (ERK)1/2 signalling plays a critical role in synaptic and structural plasticity. Recent preclinical and human brain studies suggest that depression and suicidal behaviour are associated with aberrant ERK1/2 signalling. MEK, is a dual-specificity kinase, which is the immediate upstream regulator of ERK1/2. Two isoforms of MEK (MEK1 and MEK2) exist. By phosphorylating at Ser and Thr residues, MEK activates ERK1/2, which then phosphorylates cytoplasmic and nuclear substrates. On the other hand, MEK itself is regulated through phosphorylation by upstream Raf kinases. Recently, we demonstrated that activation of ERK1/2 and B-Raf was attenuated in the brains of suicide subjects. To further investigate the regulation of ERK1/2 signalling, we examined the expression and activation of MEKs, the interaction of MEK with ERKs, MEK-mediated activation of ERK1/2, and ERK1/2-mediated activation of nuclear substrate Elk-1 in the prefrontal cortex and hippocampus of suicide subjects. In addition, in order to investigate whether MEK is regulated by B-Raf, we examined the B-Raf and MEK interaction. No significant changes were observed in expression levels of MEK1 or MEK2; however, the catalytic activity of only MEK1 (not MEK2) was decreased in both the prefrontal cortex and hippocampus of suicide subjects. The interaction of MEK1 with ERK1 and ERK2 was increased along with decreased phosphorylation and catalytic activity of ERK1/2. In addition, we found decreased phosphorylation of MEK1 and less interaction of B-Raf with MEK1. Our results demonstrate abnormalities in MEK1 at multiple levels and suggest that these abnormalities in MEK1 are crucial for aberrant ERK1/2 signalling in suicide brain.